RESEARCH WORK OF STUDENTS IN THE FIELD OF NATIONAL RELATIONS - Natalya M. Belyankova (Высшее образование в России, 2016)
The article focuses on the problem of preparing future teachers of primary school to conduct a special work aimed at harmonization of interethnic relations between pupils. The author suggests suitable topics for students’ research works. The author believes that this work should begin from the very beginning of children staying at school, and the teacher should be ready to work in the classes with ethnic diversity staff. While preparing research works on this topic students can look deeper into the problems of international relations, and also to change their own outlook. The article also discusses the difficulties that students and their supervisors may face while preparing research papers.